Parenting in place: young children's living arrangement and migrants' sleep health in South Africa - Madhavan, Sangeetha; Kim, Seung Wan; White, Michael; Gomez‐Olive, Xavier (Wiley, 2023)
Migration research tends to treat childrearing as a secondary role for migrants. By prioritising the economic objectives of migration, most models present migrants as either delaying childbearing or, if they have young children, not living with them. However, migration has become increasingly feminised, the types of mobility more varied, while the returns to migration remain uncertain at best. At the same time, norms around childrearing are shifting, and the capacity of kin to take care of children may be weakening. In such contexts, migrants may not want to or be able to be separated from their children. Confronting such difficult decisions and their consequences may be reflected in poor sleep health for the migrant parent. We draw on data from the Migration and Health Follow‐Up Study (MHFUS) in South Africa to examine the following questions: (i) To what extent is children's coresidence associated with sleep health for migrant parents? (ii) Do effects vary by sex of migrant? and (iii) Do effects vary by location of migrant? Results from propensity score matching confirm that migrants who coreside with all their young children are more likely to experience healthy sleep compared to those who have nonresident or no young children. However, stratified analysis shows that these effects are only significant for women and those not living in Gauteng province. The value of these findings is underscored by the need for research on the well‐being of migrant parents who are negotiating multiple agendas in economically precarious and physically insecure destinations.
Keywords: Childbearing; Migration; Parenting; Sleep; South Africa; SDG-5: Gender equality; SDG-10: Reduced inequalities